2020
DOI: 10.21203/rs.3.rs-18484/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between Fasting Blood Glucose Level at Admission and Mortality in COVID-19 Patients: A Retrospective Study

Abstract: Background: Coronavirus disease-19 (COVID-19) has spread rapidly, with a growing number of cases confirmed around the world. This study explores the relationship of fasting blood glucose (FBG) at admission with mortality.Methods: In this retrospective, single-center study, we analyzed the clinical characteristics of confirmed cases of COVID-19 in Wu Han from 29 January 2020 to 23 February 2020. Cox proportional hazard regression analysis was performed to evaluate the relationship between FBG and mortality.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
5
2
Order By: Relevance
“…Although the potential non-linear association between admission FBG level with poor composite and mortality outcomes remained unexplored due to paucity of studies, we were able to establish non-linear relationship between admission FBG level and severity. However, in contrast with Zhu et al [34], we did not observe a J-shaped association between admission FBG and COVID-19 severity, which may be explained by the fact that all but one study [34] reported only three categories. Despite this, our findings were in accordance with a study by Alahmad et al [44] which stated that the association between admission FBG and ICU admission was logarithmic, thus further corroborating our premises.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the potential non-linear association between admission FBG level with poor composite and mortality outcomes remained unexplored due to paucity of studies, we were able to establish non-linear relationship between admission FBG level and severity. However, in contrast with Zhu et al [34], we did not observe a J-shaped association between admission FBG and COVID-19 severity, which may be explained by the fact that all but one study [34] reported only three categories. Despite this, our findings were in accordance with a study by Alahmad et al [44] which stated that the association between admission FBG and ICU admission was logarithmic, thus further corroborating our premises.…”
Section: Discussioncontrasting
confidence: 99%
“…GRADE assessments of the prognostic value of FBG resulted in high-quality evidence for severity and moderate-quality evidence for mortality and poor outcome, whereas the remaining domains yielded very low-to-low-quality evidence. Overlapping populations were observed in four studies [32][33][34][35] (Appendix Table S7), and analyses were prioritized to Wang et al [32] due to larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential non-linear association between admission FBG level with poor composite and mortality outcomes remained unexplored due to paucity of studies, we were able to establish non-linear relationship between admission FBG level and severity. However, in contrast with Zhu et al 37 , we did not observe a J-shaped association between admission FBG and COVID-19 severity, which may be explained by the fact that all but one study 37 reported only three categories.…”
Section: Discussioncontrasting
confidence: 99%
“…‡ Subgroup analysis based on study design and location were not possible as all included studies were retrospective and conducted in China. § Overlapping populations were observed between Li et al 38 , Wang et al 35 , Zhang et al 36 , and Zhu et al 37 , of which Wang et al 35 was prioritized for analysis due to larger sample size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation